2022
DOI: 10.2147/copd.s372991
|View full text |Cite|
|
Sign up to set email alerts
|

Sinonasal Symptoms in COPD: Burden and Associations with Clinical Markers of Disease

Abstract: Purpose Sinonasal symptoms are prevalent in COPD, and knowledge of the relationship between these symptoms and clinical markers of COPD is limited. This study explores the associations between the burden of sinonasal symptoms and clinical markers and thresholds recommended for guiding treatment decisions in the GOLD guidelines. Patients and Methods Sinonasal symptoms were quantified with the rhinological subscale of the Sino-Nasal-Outcome-Test (SNOT-22) in 93 COPD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Individuals with symptoms alone may include those with other conditions, such as rhinitis, that have symptoms similar to CRS and that have been shown to be associated with COPD. 32 The average age of respondents at CRISP1 was 55 years. This is the age at which we determined CRS status, not the age of CRS onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with symptoms alone may include those with other conditions, such as rhinitis, that have symptoms similar to CRS and that have been shown to be associated with COPD. 32 The average age of respondents at CRISP1 was 55 years. This is the age at which we determined CRS status, not the age of CRS onset.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern did not hold for all conditions; however, most notably, symptoms alone were associated with more than twice the odds of new‐onset COPD. Individuals with symptoms alone may include those with other conditions, such as rhinitis, that have symptoms similar to CRS and that have been shown to be associated with COPD 32 …”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the sinonasal symptoms and the severity of respiratory symptoms was evaluated in COPD patients, and it was found that a high burden of sinonasal symptoms is positively associated with the clinical markers of symptom severity (cough, and dyspnea) 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Initial observations of the coexistence of allergic rhinitis, chronic rhinosinusitis, and asthma led to the formulation of the concept of united airways diseases (UAD) 3 . Both the upper and lower airways share macroscopic and microscopic pathological features, with a similar allergic response in rhinitis and asthma 4 .…”
Section: Introductionmentioning
confidence: 99%